Impact of Structural Empowerment on the Work Engagement of Non-managerial Nurses, by Years of Experience - Shingu, Hiroyuki; Ambo, Hiroaki; Takaya, Shin (Journal of Japan Academy of Nursing Science, 2025)
Purpose: In this study, we aimed to examine the relationship between work engagement and subscales of structural empowerment among non-managerial nurses, by years of experience.Method: A questionnaire survey was conducted on work engagement and structural empowerment among 1,053 nurses working at 12 hospitals in Prefecture A and ordinance-designated city B in the Tohoku region of Japan. A hierarchical multiple regression analysis was conducted on the non-managerial nurses.Results: The study included 397 non-managerial nurses. Among the subscales of structural empowerment, “Information” and “Support” were significantly related to work engagement among nurses with less than three years of experience, “Opportunity” was significantly related to work engagement among nurses with four to nine years of experience, and “Resources” and “Informal Power” were significantly related to work engagement among nurses with more than ten years of experience.Discussion: The subscales of structural empowerment that contribute to improving the work engagement of non-managerial nurses differ depending on the number of years of experience. Therefore, measures tailored to the number of years of experience are required.